Pieter Potgieter as mens en teoloog: essensieel en eietyds - S. A. Strauss (Acta Theologica)
This article focuses on the life and work of Pieter Potgieter. A few of his most important publications are analysed, in order to evaluate his theological contribution. He concentrated on substantial and essential Biblical principles, and their application in our times. He devoted himself to researching especially the following: the doctrines of Scripture, the church and providence as well as the theology of Calvin. Furthermore, he is widely respected for the outstanding leading role he played in the church on both synodical and ecumenical levels. As a born leader this was a task for which he had a natural aptitude. A complete bibliography of Potgieter concludes this article.